Correlation between Hard and Soft Tissue Lower Anterior Facial Height of Different Skeletal Pattern on South Indian Population - Seerab Husain1 , Naveen Kumar2 , Sri Rengalakshmi2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The soft tissue is in close contact to the underlying skeletal hard tissue and takes up whatever form isdictated by the hard tissue. Yet, there exists some variations in cases of which, the soft tissue thickness variesin certain places to camouflage the skeletal deficiency. Hence, the purpose of this study was to evaluatethe correlation of hard and soft tissue lower anterior facial height (LAFH) of different skeletal patternson the south indian population. The study consisted of 30 lateral cephalograms, which were divided intothree groups based on the skeletal relationship: Group A - Class I skeletal pattern, Group B - Class IIskeletal pattern and Group C - Class III skeletal pattern. All the groups contained 10 radiographs each of thatparticular skeletal pattern. FACAD software was used to do the digital tracing and analysis. The obtainedresults were tabulated and were subjected to statistical analysis using SPSS software version 23. The resultsof Pearson’s correlation test revealed that Group A and Group B were positively correlated with statisticalsignificance, whereas Group C was statistically insignificant. Hence, soft tissue LAFH can be used as avaluable indicator and an adjunct in diagnosis and treatment planning of orthodontic cases.